Analisis Persepsi Dan Sentimen Wisatawan Dalam Instagram Sebagai Masukan Pengembangan Pantai Klayar Kabupaten Pacitan - Wulandari, Novi; Widyaningsih, Yulia Arisnani (JURNAL DESTINASI PARIWISATA, 2023)
Social media is a digital technology that is useful as a forum to share various tourist opinions. It influences perceptions towards tourism destinations. This perception can contain information needed by other tourists and tourism destination stakeholders to make decisions. This study aims to identify and analyze tourist sentiment based on perceptions on Instagram regarding the Klayar Beach in Pacitan Regency and identify responses and strategies for destination managers. This type of research is a descriptive analysis research using a qualitative approach. The techniques used for data collection in this study were observations and interviews. Data was obtained from tourist comments on Instagram social media regarding the Klayar Beach Pacitan Regency. The data used in this study were obtained from the Instagram account @pacitanku from June 2021 to June 2022. The tourist perception data was then processed using RStudio with the R programming language. The opinions on Klayar Beach can be classified the natural beauty of Klayar Beach, Access to Klayar Beach, Tourist Experience, Revisit Intention, Disappointment, Klayar Beach Facilities and Infrastructure. Furthermore, the results of media content to social media managers, trying to meet the needs of tourists and taking advantage of tourist participation in Klayar Beach marketing promotions. Keywords: Digital Marketing; Social Media; Perception